Halide solid electrolyte material and preparation method thereof, solid electrolyte membrane and lithium ion battery
The solution preparation of LixTayInzCl6 halide solid electrolyte material was solved, and the problem of difficulty in large-scale preparation of Ta-based halide solid electrolyte materials was achieved, and high-performance and low-cost lithium-ion conductivity materials were achieved.
Patent Information
- Application Number
- CN202411362668.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2024-12-20
AI Technical Summary
The existing Ta-based halide solid electrolyte materials are difficult to prepare on a large scale, and the traditional solid-phase reaction methods have problems of high cost and low yield.
The chemical formula of LixTayInzCl6 halide solid electrolyte material was prepared by solution method, and the y/x ratio was controlled to be 0.04-1, z=(6-x-5y)/3, 1>z>0.2, using anhydrous alcohol solvent and heat treatment A high-performance phase is obtained.
The preparation of halide solid electrolyte materials with high lithium ion conductivity has been achieved, reducing the preparation cost and is suitable for large-scale production.
Smart Images

Figure CN119170864A_ABST
Abstract
Description
[0001] This application is a divisional application. The application number of the original application is: 202410716645.9, the application date is June 4, 2024, and the name of the invention is: Halide solid electrolyte material and preparation method thereof, solid electrolyte membrane and lithium-ion battery. Technical Field
[0002] The present application relates to the field of battery technology, and in particular to a halide solid electrolyte material and a preparation method thereof, a solid electrolyte membrane and a lithium ion battery. Background Art
[0003] Solid-state electrolytes have the advantages of safety, stability, and high-voltage resistance, and play a vital role in lithium-ion batteries.
[0004] In the current solid electrolyte system, halide solid electrolyte materials have attracted much attention due to their good stability to the positive electrode. In order to better realize the commercialization of materials and promote the development of solid electrolytes, it is urgent to develop halide solid electrolyte materials with higher performance. Summary of the invention
[0005] The embodiments of the present application provide a halide solid electrolyte material and a preparation method thereof, a solid electrolyte membrane and a lithium ion battery, which have high lithium ion conductivity.
[0006] In a first aspect, the present invention provides a halide solid electrolyte material, wherein the chemical formula of the halide solid electrolyte material is Li x Ta y In z Cl 6 , where y / x=0.04~1, z=(6-x-5y) / 3, 1>z>0.2.
[0007] Optionally, in some embodiments of the present application, y / x=0.2-0.6; and / or,
[0008] The ionic conductivity of the halide solid electrolyte material is greater than or equal to 1 mS / cm; and / or,
[0009] The average particle size of the halide solid electrolyte material is 1 to 5 μm.
[0010] Optionally, in some embodiments of the present application, the ionic conductivity of the halide solid electrolyte material is 1 to 3 mS / cm.
[0011] Optionally, in some embodiments of the present application, the halide solid electrolyte material is selected from Li 2 Ta 0.5 In 0.5 Cl6 , Li 1.6 Ta 0.7 In 0.3 Cl 6 , Li 1.2 Ta 0.9 In 0.1 Cl 6 , Li 2.8 Ta 0.1 In 0.9 Cl 6 One or more of .
[0012] In a second aspect, an embodiment of the present application provides a method for preparing a halide solid electrolyte material, comprising the following steps:
[0013] providing a first mixture comprising lithium chloride, indium chloride, tantalum chloride, and an anhydrous alcohol solvent;
[0014] heating the first mixture to obtain crystals;
[0015] The crystal is heat-treated to obtain a halide solid electrolyte.
[0016] Optionally, in some embodiments of the present application, the molar ratio of Li in the lithium chloride, Ta in the tantalum chloride and In in the indium chloride is x:y:z, wherein y / x=0.04-1, z=(6-x-5y) / 3, 1>z>0.2; and / or,
[0017] The anhydrous alcohol solvent includes one or more anhydrous alcohol solvents having 1 to 8 carbon atoms; the anhydrous alcohol solvents having 1 to 8 carbon atoms include one or more of anhydrous methanol, anhydrous ethanol, anhydrous propanol, anhydrous butanol, anhydrous pentanol, anhydrous hexanol, anhydrous heptanol, anhydrous ethylene glycol, and anhydrous glycerol; and / or,
[0018] The lithium chloride, the indium chloride and the tantalum chloride are solid phase materials, and the volume of the anhydrous alcohol solvent added per gram of the solid phase material is 10 to 50 mL.
[0019] Optionally, in some embodiments of the present application, in the step of heating the first mixture to obtain crystals, the heating temperature is 60-100° C.; and / or,
[0020] In the step of heating the first mixture to obtain crystals, the heating time is 1 to 10 hours; and / or,
[0021] The step of providing a first mixture containing lithium chloride, indium chloride, tantalum chloride and anhydrous alcohol solvent comprises: mixing lithium chloride, indium chloride, tantalum chloride and anhydrous alcohol solvent, and heating at 50-70° C. for 2-10 hours.
[0022] Optionally, in some embodiments of the present application, in the step of heat treating the crystal to obtain a halide solid electrolyte,
[0023] The heat treatment temperature is 120-250° C.; and / or,
[0024] The heating time is 2 to 12 hours; and / or,
[0025] The heat treatment is carried out under vacuum conditions, and the vacuum degree is 0.5×10 -3 ~2×10 -3 Torr.
[0026] In a third aspect, an embodiment of the present application provides a solid electrolyte membrane, wherein the material of the solid electrolyte membrane includes the halide solid electrolyte material described above, or the halide solid electrolyte material prepared by the preparation method described above.
[0027] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet arranged opposite to each other, and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte membrane comprises the solid electrolyte membrane described above.
[0028] The technical solution provided in the present application provides a new halide solid electrolyte material, which has good ionic conductivity and can be prepared by a solution method. The preparation process is simple and the preparation cost is low, and large-scale production requirements can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 A schematic flow chart of a method for preparing a halide solid electrolyte material provided in an embodiment of the present application;
[0031] Figure 2 is an X-ray diffraction analysis spectrum of the halide solid electrolyte material prepared in Example 1;
[0032] Figure 3 This is the electrochemical impedance test curve of the halide solid electrolyte material prepared in Example 1. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art, and the materials or reagents used in the examples and comparative examples of the present application are commercially available. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present application. The preferred implementation methods and materials described herein are for demonstration purposes only and cannot limit the content of the present application.
[0035] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. The various embodiments of the present application may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0036] In the description of the present application, the term “including” means “including but not limited to”.
[0037] The terms "multiple", "multiple times" or similar expressions refer to two (times) or more than two (times), for example, it can be two (times), three (times), four (times), five (times), six (times), etc.
[0038] The selection scope of the term "and / or" includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, and the said any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions of A, B and A+B. For another example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution connected by "logical or"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four items of A, B, C, and D (that is, the technical solution connected by "logical and").
[0039] The term "solid content" refers to the ratio of the mass of solid matter in the slurry to the total mass of the slurry.
[0040] Ta-based halide electrolytes such as LiTaCl 6 and LiTaOCl 4 The preparation of Ta-based halide electrolyte materials requires tantalum chloride (TaCl 5 ), lithium chloride (LiCl) and other raw materials, however, due to TaCl 5 The melting and boiling points of Ta are very different from those of LiCl, and there is a glass phase in the high-performance phase. It is difficult to obtain high-performance phases by traditional solid-phase reaction methods. Therefore, Ta-based halide electrolytes are generally achieved by high-energy ball milling combined with annealing process. However, high-energy ball milling requires high-cost instruments and equipment, and the output of one ball milling is extremely low (the output is about 1 to 3g), which is only suitable for small laboratory scale. At present, Ta-based halide electrolytes are difficult to prepare on a large scale.
[0041] In a first aspect, the present invention provides a halide solid electrolyte material, wherein the chemical formula of the halide solid electrolyte material is Li x Ta y In z Cl 6 . Wherein, x, y, and z need to satisfy the following conditions: In some embodiments, the ratio of y to x, i.e., y / x, is in the range of 0.04 to 1, for example, y / x can be 0.04, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, and values between any two of the above values; In some embodiments, the relationship between x, y, and z can satisfy: z = (6-x-5y) / 3, and 1>z>0.2.
[0042] The halide solid electrolyte material having the above chemical formula and x, y, and z satisfying the above conditions not only has better ionic conductivity, but also can be prepared with a solution method preparation process to produce the material with a high-performance phase. The preparation process is simple, the preparation cost is low, and large-scale production requirements can be achieved.
[0043] In some embodiments, y / x is further selected from a value in the range of 0.2 to 0.6, for example, it can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 and values between any two of the above values; when y / x is selected within the above range, it is beneficial to further improve the performance of the material.
[0044] In some embodiments, the ionic conductivity of the halide solid electrolyte material is greater than or equal to 1mS / cm; the halide solid electrolyte material has a better ionic conductivity and can be used to prepare a solid electrolyte membrane of a lithium battery to obtain a lithium battery with better performance. In other embodiments, the ionic conductivity of the halide solid electrolyte material can also reach 1 to 3mS / cm, such as 1mS / cm, 1.5mS / cm, 2mS / cm, 2.5mS / cm, 3mS / cm and values between any two of the above values. The ionic conductivity can be detected by an electrochemical workstation commonly used in the art.
[0045] In some embodiments, the average particle size of the halide solid electrolyte material is 1 to 5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, and a value between any two of the above values.
[0046] In some specific embodiments, the halide solid electrolyte material is selected from Li 2 Ta 0.5 In 0.5 Cl 6 , Li 1.6 Ta 0.7 In 0.3 Cl 6 , Li 1.2 Ta 0.9 In 0.1 Cl 6 , Li 2.8 Ta 0.1 In 0.9 Cl 6 The halide solid electrolyte material has good ionic conductivity.
[0047] In the second aspect, the present application also proposes a method for preparing a halide solid electrolyte material, see Figure 1 , the preparation method comprises the following steps:
[0048] S10, providing a first mixture comprising lithium chloride, indium chloride, tantalum chloride and an anhydrous alcohol solvent;
[0049] S20, heating the first mixture to obtain crystals;
[0050] S30, heat-treating the crystal to obtain a halide solid electrolyte material.
[0051] The preparation method of this embodiment has low requirements on equipment. The required halide solid electrolyte material can be successfully prepared by conventional experimental equipment without the need for high-cost high-energy ball milling equipment. The preparation method of this embodiment can prepare kilogram-level halide solid electrolyte materials, which is suitable for industrial mass production. The halide solid electrolyte material prepared by the method of this embodiment has a high level of lithium ion conductivity.
[0052] In some embodiments, the chemical formula of the material prepared by the preparation method of the present application is Li x Ta y In z Cl 6 . And x, y, z satisfy y / x=0.04~1, z=(6-x-5y) / 3, 1>z>0.2.
[0053] The anhydrous alcohol solvent refers to an anhydrous alcohol reagent, which has very little or no water content. In some embodiments, the water content in the anhydrous alcohol solvent can be less than or equal to 0.5 (v / v)%, and in other embodiments, the water content can also be less than or equal to 0.1 (v / v)%. Lithium chloride, indium chloride and tantalum chloride can be stably present and well dispersed and dissolved in the anhydrous alcohol solvent, which helps to form a stable halide solid electrolyte material later.
[0054] In some specific embodiments, the anhydrous alcohol solvent may include one or more anhydrous alcohol solvents having 1 to 8 carbon atoms, that is, alcohols having 1, 2, 3, 4, 5, 6, 7 or 8 carbon atoms or their derivatives; for example, the anhydrous alcohol solvents having 1 to 8 carbon atoms may include, but are not limited to, one or more of anhydrous methanol, anhydrous ethanol, anhydrous propanol, anhydrous butanol, anhydrous pentanol, anhydrous hexanol, anhydrous heptanol, anhydrous ethylene glycol, and anhydrous glycerol. The anhydrous alcohol solvents may be purchased on the market.
[0055] The feed amounts of the lithium chloride, indium chloride and tantalum chloride can satisfy: the molar ratio of Li in the lithium chloride, Ta in the tantalum chloride and In in the indium chloride is x:y:z, wherein the ratio of y to x, i.e. y / x, is in the range of 0.1 to 1, for example, y / x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 and any two values between the above; z = (6-x-5y) / 3, and 1>z>0.2. Controlling the feed amount within the above range is conducive to forming a pure substance with stable composition and high performance, and reducing the appearance of impurities.
[0056] The amount of the anhydrous alcohol solvent used can meet the following conditions. For example, if the lithium chloride, the indium chloride and the tantalum chloride are called solid phase materials, the volume of the anhydrous alcohol solvent added per gram of the solid phase material is 10 to 50 mL. That is to say, when the total mass of the lithium chloride, the indium chloride and the tantalum chloride is W (in grams), the amount of the anhydrous alcohol solvent added is 10×W mL to 50×W mL.
[0057] In some embodiments, in step S10, the first mixture can be obtained by dissolving the solid phase material in an anhydrous alcohol solvent. For example, step S10 may specifically include: mixing lithium chloride, indium chloride, tantalum chloride and an anhydrous alcohol solvent, and heating at 50-70°C for 2-10 hours. In order to better dissolve the solid phase material, the mixing step can be performed under a certain temperature environment, and the temperature can be 50-70°C, such as 50°C, 55°C, 60°C, 65°C, 70°C and values between any two of the above values; the mixing time can be 2-10 hours; for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and values between any two of the above values.
[0058] In step S20, the first mixture is heated to volatilize and remove excess solvent in the system to obtain Li x Ta y In z Cl 6 -Crystals of ROH, wherein ROH refers to all organic components in the crystallized product, such as alcohols.
[0059] In some embodiments, in the step of heating the first mixture to obtain crystals, the heating temperature is 60-100°C; for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, and values between any two of the above values.
[0060] In some embodiments, in the step of heating the first mixture to obtain crystals, the heating time is 1 to 10 hours; for example, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, and values between any two of the above values.
[0061] In step S30, the crystal is further subjected to heat treatment to remove organic components such as ROH in the crystal to obtain Li x Ta y In z Cl 6 Halide solid electrolyte.
[0062] In some embodiments, the temperature of the heat treatment is 120-250°C; for example, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C and values between any two of the above values.
[0063] In some embodiments, the heating time is 2 to 12 hours; for example, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, and values between any two of the above values.
[0064] In some embodiments, the heat treatment is performed under vacuum conditions, and the vacuum degree is 0.5×10 -3 ~2×10 - 3 Torr; for example, it can be 0.5×10 -3 Torr, 0.6×10 -3 Torr, 0.7×10 -3 Torr, 0.8×10 -3 Torr, 0.9×10 - 3 Torr, 1×10 -3 Torr, 1.2×10 -3 Torr, 1.4×10 -3 Torr, 1.5×10 -3 Torr, 1.8×10 -3 Torr, 2×10 - 3 Torr and values between any two of the above values.
[0065] In a third aspect, the embodiments of the present application also provide a solid electrolyte membrane that can be used in a lithium-ion battery. The material of the solid electrolyte membrane includes the halide solid electrolyte material as described above, or the halide solid electrolyte material prepared by the preparation method described above. The halide solid electrolyte material has the characteristics and corresponding effects of all the embodiments described above, based on which, the solid electrolyte membrane has better ionic conductivity and is easy to prepare.
[0066] In a fourth aspect, the embodiments of the present application provide a lithium-ion battery, including but not limited to button batteries, soft-pack batteries, square lithium-ion batteries, cylindrical lithium-ion batteries, etc. The lithium-ion battery includes a positive electrode sheet and a negative electrode sheet arranged opposite to each other, and a solid electrolyte membrane as described in any of the embodiments above, wherein the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet.
[0067] The technical scheme and technical effects of the present application are described in detail below through specific embodiments. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0068] Example 1
[0069] The solid electrolyte material Li x Ta y In z Cl 6 In, y / x=0.25, z=(6-x-5y) / 3, specifically, x=2, y=0.5, z=0.5.
[0070] (I) The preparation steps of solid electrolyte materials are as follows:
[0071] 1. Weigh 2g of LiCl and TaCl according to the stoichiometric ratio. 5 、InCl 3 Chemical raw materials, the raw material ratio is: LiCl, TaCl 5 、InCl 3 The molar ratio is 2:0.5:0.5;
[0072] 2. Add the above weighed chemical raw materials into 30 mL of anhydrous ethanol in sequence;
[0073] 3. Heat the mixed solution to 50°C and stir magnetically for 2 hours;
[0074] 4. Place the stirred mixed solution in a 60°C oven and dry until crystals appear and no ethanol remains. The obtained crystals are the precursor product of the halide electrolyte;
[0075] 5. Place the dried precursor in a vacuum drying oven for 10 -3Torr, heat treatment at 180 ° C for 4 h to remove the organic components in the crystalline product to obtain a solid electrolyte material Li with an average particle size of about 3 μm 2 Ta 05 In 05 Cl 6 .
[0076] (II) Preparation of solid electrolyte membrane
[0077] 1. Take 100 mg of the solid electrolyte material powder prepared by the above process and place it in a customized PEEK mold with a diameter of 10 mm. The assembly process is carried out in an argon glove with a water content of less than 0.01 ppm;
[0078] 2. After the above mold is subjected to a pressure of 300 MPa for ~1 min, the densification of the halide electrolyte can be achieved and the lithium ion conductivity test can be performed.
[0079] Take the product obtained in step (a) - solid electrolyte material Li 2 Ta 0.5 In 0.5 Cl 6 Test; use X-ray diffractometer to perform X-ray diffraction analysis on the material, the results are as follows Figure 2 As shown in the figure, it can be seen that the main phase of the phase and Li 3 InCl 6 The standard card can be well matched, and some of the impurity peaks may be related to TaCl 5 Related to air contamination of samples;
[0080] In order to obtain the lithium ion conductivity of the material, the above material was pressed into a tablet and then sent to an electrochemical workstation for electrochemical impedance testing. The test frequency range was 1 Hz to 10 MHz. After testing, the electrochemical impedance test curve was as follows: Figure 3 As shown in the figure, the lithium ion conductivity of the material can be calculated to be 2.03mS / cm. Among them, electrochemical impedance is a vector, often written in complex form, which is composed of a real part and an imaginary part. Figure 3 In the equation, Z' represents the real part of the impedance and -Z" represents the negative of the imaginary part of the impedance.
[0081] Example 2
[0082] This embodiment is basically the same as embodiment 1, except that in step (1) of this embodiment, LiCl, TaCl 5 、InCl 3 The total mass of the chemical raw materials was changed to 30 g, and the amount of anhydrous ethanol was adjusted to 900 mL accordingly. Other parameters and steps remained unchanged.
[0083] Example 3
[0084] This embodiment is basically the same as embodiment 1, except that in step (1) of this embodiment, LiCl, TaCl 5 、InCl 3 The total mass of the chemical raw materials was changed to 100 g, and the amount of anhydrous ethanol was adjusted to 1500 mL accordingly. Other parameters and steps remained unchanged.
[0085] Example 4
[0086] This embodiment is basically the same as the embodiment 1, except that the element composition of the target product halide solid electrolyte material in this embodiment is the raw material ratio parameter x=2.8, y=0.1, z=0.9; accordingly, in step (1) of this embodiment, the raw material ratio is: LiCl, TaCl 5 、InCl 3 The molar ratio of 2.8:0.1:0.9 was 2.8:0.1:0.9. Other parameters and steps remained unchanged.
[0087] Example 5
[0088] This example is substantially the same as Example 1, except that in step (1) of this example, the volume of anhydrous ethanol is changed to 15 mL. Other parameters and steps remain unchanged.
[0089] Example 6
[0090] This embodiment is substantially the same as embodiment 1, except that in step (1) of this embodiment, the volume of anhydrous ethanol is changed to 100 mL. Other parameters and steps remain unchanged.
[0091] Example 7
[0092] This embodiment is basically the same as the embodiment 1, except that in step (1) of this embodiment, the heat treatment temperature is changed from 180° C. to 100° C. Apart from this, the other parameters and steps remain unchanged.
[0093] Comparative Example 1
[0094] This comparative example is basically the same as Example 1, except that the element composition of the target product halide solid electrolyte material of this comparative example is the raw material ratio parameter x=1, y=1.2 (y / x=1.2), z=0.1; accordingly, in step (1) of this comparative example, the raw material ratio is: LiCl, TaCl 5 、InCl 3 The molar ratio of LiTa is 1:1.2:0.1. Other parameters and steps remain unchanged. The product formed after step (1) in this comparative example may not be a pure substance, but contain multiple impurities. Its nominal composition may be LiTa1.2 In 0.1 Cl 6 .
[0095] Comparative Example 2
[0096] This comparative example is basically the same as Example 1, except that the element composition of the target product halide solid electrolyte material of this comparative example is the raw material ratio parameter x=1.2, y=0.9 (y / x=0.75), z=0.1; accordingly, in step (i) of this comparative example, the raw material ratio is: LiCl, TaCl 5 、InCl 3 The molar ratio of 1:1 is 1.2:0.9:0.1. Other parameters and steps remain unchanged.
[0097] Comparative Example 3
[0098] This comparative example is basically the same as Example 1, except that the element composition of the target product halide solid electrolyte material of this comparative example is the raw material ratio parameter x=1, y=1, z=0; accordingly, in step (i) of this comparative example, indium chloride is not added to the raw material, and the raw material ratio is: LiCl, TaCl 5 The molar ratio of is 1: 1. Apart from this, the other parameters and steps remain unchanged.
[0099] Comparative Example 4
[0100] This comparative example is basically the same as Example 1, except that in step (1) of this comparative example, InCl 3 Chemical raw materials changed to LaCl 3 , accordingly, the nominal composition of the solid electrolyte material in this embodiment may be Li 2 Ta 0.5 La 0.5 Cl 6 Apart from this, all other parameters and steps remain unchanged.
[0101] Comparative Example 5
[0102] This comparative example is basically the same as Example 1, except that in step (1) of this comparative example, TaCl 5 Chemical raw materials changed to LaCl 3 , accordingly, the nominal composition of the solid electrolyte material in this embodiment may be Li 3 La 0.5 In 0.5 Cl 6 Apart from this, all other parameters and steps remain unchanged.
[0103] Comparative Example 6
[0104] This comparative example is substantially the same as Example 1, except that in step (i) of this example, anhydrous ethanol is replaced by an ethanol solution having a volume concentration of 75 (v / v)%. In addition, other parameters and steps remain unchanged. In step (i) of this comparative example, after the chemical raw materials are added to the ethanol solution, a precipitate appears, and the raw materials cannot stably exist in the solution system, and it is difficult to subsequently form a crystal with a stable composition, so the synthesis step is terminated.
[0105] Experimental example
[0106] The halide solid electrolyte materials prepared in the above Examples 1 to 7 and Comparative Examples 1 to 5 were tested for ion conductivity, and the results were recorded in Table 1. The ion conductivity testing method can refer to the testing method in Example 1.
[0107] Table 1
[0108]
[0109]
[0110] It can be seen from the above table:
[0111] In Examples 1 to 3, as the amount of raw material input increases, the yield of the product halide solid electrolyte material increases accordingly, indicating that the method of the present application can prepare a product with a large yield and can be suitable for large-scale production;
[0112] Compared with Comparative Examples 1 and 2, Examples 1 to 7 all have higher ionic conductivity, while the two comparative examples show extremely low ionic conductivity, indicating that when x, y, and z satisfy y / x=0.04-1, z=(6-x-5y) / 3, and 1>z>0.2, it is conducive to the formation of high-performance materials; further, in the embodiments, Example 1 shows the best ionic conductivity, and in comparison, the ionic conductivity of Examples 4 to 7 is relatively low, indicating that when y / x is in the range of 0.2-0.6, the amount of anhydrous alcohol solvent is controlled to be 10-50 mL / g of solid phase material, and the heat treatment temperature is 120-250°C, it is more conducive to the improvement of material performance;
[0113] Comparative Examples 3 to 4 all showed ionic conductivity much lower than that of Example 1, which may be because the incorporation of In can promote the reaction to proceed in the forward direction, and during the heating and heat treatment stages, the stable existence of the product structure can be ensured, thereby obtaining a high-performance material;
[0114] In Comparative Example 5, Ta is replaced by La. Although an electrolyte material with certain performance can be prepared, its ion conductivity is relatively low, far lower than the ion conductivity level of Example 1, indicating that the combination of Li, Ta, and In is more conducive to forming a high-performance and stable material;
[0115] In addition, Comparative Example 6 was terminated because the raw materials could not stably exist in the ethanol solution, indicating that the use of anhydrous alcohol solvents as the solvent of the solution system in the embodiments of the present application is conducive to the stable existence and dissolution of the raw materials, and helps the subsequent reactions to obtain materials with stable composition.
[0116] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A halide solid electrolyte material, characterized in that: The chemical formula of the halide solid electrolyte material is Li 1.2 Ta 0.9 In 0.1 Cl6 or Li 2.8 Ta 0.1 In 0.9 Cl6.
2. The halide solid electrolyte material according to claim 1, characterized in that The ionic conductivity of the halide solid electrolyte material is greater than or equal to 1 mS / cm; and / or, The average particle size of the halide solid electrolyte material is 1 to 5 μm.
3. The halide solid electrolyte material according to claim 2, characterized in that: The ion conductivity of the halide solid electrolyte material is 1-3 mS / cm.
4. A method for preparing a halide solid electrolyte material according to any one of claims 1 to 3, characterized in that: The following steps are involved: providing a first mixture comprising lithium chloride, indium chloride, tantalum chloride, and an anhydrous alcohol solvent; heating the first mixture to obtain crystals; The crystal is subjected to heat treatment to obtain a halide solid electrolyte material.
5. The preparation method according to claim 4, characterized in that: The anhydrous alcohol solvent includes one or more anhydrous alcohol solvents having 1 to 8 carbon atoms; the anhydrous alcohol solvents having 1 to 8 carbon atoms include one or more of anhydrous methanol, anhydrous ethanol, anhydrous propanol, anhydrous butanol, anhydrous pentanol, anhydrous hexanol, anhydrous heptanol, anhydrous ethylene glycol, and anhydrous glycerol; and / or, The lithium chloride, the indium chloride and the tantalum chloride are solid phase materials, and the volume of the anhydrous alcohol solvent added per gram of the solid phase material is 10 to 50 mL.
6. The preparation method according to claim 4, characterized in that: In the step of heating the first mixture to obtain crystals, the heating temperature is 60 to 100° C.; and / or, In the step of heating the first mixture to obtain crystals, the heating time is 1 to 10 hours; and / or, The step of providing a first mixture containing lithium chloride, indium chloride, tantalum chloride and anhydrous alcohol solvent comprises: mixing lithium chloride, indium chloride, tantalum chloride and anhydrous alcohol solvent, and heating at 50-70° C. for 2-10 hours.
7. The preparation method according to claim 4, characterized in that: In the step of heat treating the crystal to obtain a halide solid electrolyte material, The heat treatment temperature is 120-250° C.; and / or, The heating time is 2 to 12 hours; and / or, The heat treatment is carried out under vacuum conditions, and the vacuum degree is 0.5×10 -3 ~2×10 -3 Torr.
8. A solid electrolyte membrane, characterized in that: The material of the solid electrolyte membrane includes the halide solid electrolyte material according to any one of claims 1 to 3, or the halide solid electrolyte material prepared by the preparation method according to any one of claims 4 to 7.
9. A lithium ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet which are arranged opposite to each other, and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte membrane comprises the solid electrolyte membrane according to claim 8.
Citation Information
Patent Citations
Metal element doped halide solid electrolyte material and preparation method and application thereof
CN115275330A
Halide solid electrolyte and preparation method thereof
CN115642297A
Halide solid electrolyte and preparation method and application thereof
CN116031475A
Lithium-containing chloride, method for producing same, solid electrolyte, and battery
CN117642361A
